Determination Acceptance of Employees, Education, Use, Maintenance, and through Termination Department of Job Satisfaction as an Intervening Personnel Variable to Improve Performance of Regional Police in Riau Islands, Indonesia - Wibisono, Chablullah; ., Ngaliman; Cahyadi, Susetio (International Journal of Engineering and Technology, 2018)
Law No. 2 of 2002 on the National Police asserted that the Indonesian National Police is a tool that acts maintaining state security and public order, enforcing the law, and to provide protection, shelter, and services to the community to maintaining homeland security. People expect that the police can transform themselves and carry out what is the role and core functions well. By the Regulation. No. 22 of 2010 that the entire cycle of the Life Cycle Bin HR is the duty and responsibility of the Bureau of Human Resources assisted by some sections in charge and responsible for human resources Bin include: Section Control Personnel (Bagdalpers) is accountable for accepting, Education, and Termination; Career Development Section (Bagbinkar) accountable for the use; Care Personnel Section (Bagwatpers) is responsible for Nursing.Collecting the data in this study using a questionnaire in the form of surveys distributed to respondents amounted to 252 people, the number of respondents is only 200 questionnaires that can be processed from the 685 total number of active population of members of the police in Riau Islands Police subsequently transformed the data with models Structural Equation Model (SEM). The software used for structural analysis is AMOS 23 and Arbuckle and for descriptive analysis using SPSS 23.From the test results show that the variable acception (X1), education (X2), the use of (X3), treatment (X4), termination (X5) have an influence on the performance of 69.2%, and the variable acception (X1), education (X2), use (X3), treatment (X4), termination (X5) has a 58.1% effect on job satisfaction. The conclusion of this study extends from the regression weight; it turns out that the most significant care variables 47.6%. That is, the variable treatment of the most dominant influence on performance and job satisfactionÂ
Keywords: Acception; Education; Use; Maintenance; Termination; Performance And Job Satisfaction